Assessing equity in the geographical distribution of community pharmacies in South Africa in preparation for a national health insurance scheme - Kim Ward; David Sanders; Henry Leng; Allyson M Pollock (The World Health Organization, 2014)
Objective To investigate equity in the geographical distribution of community pharmacies in South Africa and assess whether regulatory reforms have furthered such equity. Methods Data on community pharmacies from the national department of health and the South African pharmacy council were used to analyse the change in community pharmacy ownership and density (number per 10 000 residents) between 1994 and 2012 in all nine provinces and 15 selected districts. In addition, the density of public clinics, alone and with community pharmacies, was calculated and compared with a national benchmark of one clinic per 10 000 residents. Interviews were conducted with nine national experts from the pharmacy sector. Findings Community pharmacies increased in number by 13% between 1994 and 2012 - less than the 25% population growth. In 2012, community pharmacy density was higher in urban provinces and was eight times higher in the least deprived districts than in the most deprived ones. Maldistribution persisted despite the growth of corporate community pharmacies. In 2012, only two provinces met the 1 per 10 000 benchmark, although all provinces achieved it when community pharmacies and clinics were combined. Experts expressed concerns that a lack of rural incentives, inappropriate licensing criteria and a shortage of pharmacy workers could undermine access to pharmaceutical services, especially in rural areas. Conclusion To reduce inequity in the distribution of pharmaceutical services, new policies and legislation are needed to increase the staffing and presence of pharmacies.